Nephrotoxicity induced by the venom of Hypnale hypnale from Sri Lanka: Studies on isolated perfused rat kidney and renal tubular cell lines. (July 2019) - Villalta, Mauren; Sampaio, Tiago Lima; de Menezes, Ramon Róseo Paula Pessoa Bezerra; Lima, Dânya Bandeira; Jorge, Antônio Rafael Coelho; Alves, Renata Sousa; Monteiro, Helena Serra Azul; Gawarammana, Indika; Maduwage, Kalana; Malleappah, Roy; León, Guillermo; Martins, Alice M.C.; et al.
Abstract: The hump-nosed pit viper Hypnale hypnale is responsible for a high number of snakebite cases in southwestern India and Sri Lanka. Although most patients only develop local signs and symptoms of envenoming, there is a growing body of evidence indicating that these envenomings may be associated with systemic alterations, including acute kidney injury. In this study we evaluated the renal toxicity of H. hypnale venom by using a perfused isolated rat kidney system and by assessing cytotoxicity in two different renal tubular cell lines in culture. The venom caused alterations in several renal functional parameters, such as reduction on perfusion pressure, renal vascular resistance, and sodium and chloride tubular transport, whereas glomerular filtration rate and urinary flow initially decreased and then increased after venom perfusion. In addition, this venom was cytotoxic to proximal and distal renal tubular cells in culture, with predominance of necrosis over apoptosis. Moreover, the venom affected the mitochondrial membrane potential and induced an increment in reactive oxygen species in these cells. Taken together, our results demonstrate a nephrotoxic activity of H. hypnale venom in these experimental models, in agreement with clinical observations. Graphical abstract: Image 1 Highlights: The nephrotoxic effect of the venom of Hypnale hypnale from Sri Lanka was investigated. Venom induced several functional alterations in the isolated rat perfused kidney. Venom was cytotoxic for proximal and distal renal epithelial cells in culture. This experimental model of nephrotoxicity agrees with clinical observations.